2021
DOI: 10.1155/2021/9230435
|View full text |Cite
|
Sign up to set email alerts
|

miR‐4454 Promotes Hepatic Carcinoma Progression by Targeting Vps4A and Rab27A

Abstract: Hepatocellular carcinoma (HCC) has high morbidity and mortality. MicroRNAs (miRNAs), which could be regulated by cancer-derived exosomes, play critical regulatory roles in the initiation and development of cancer. However, the expressions, effects, and mechanisms of abundant miRNAs regulated by HCC cancer-derived exosomes in HCC remain largely unclear. Exosomes of HepG2 cells under heat shock, TGF-β1, doxorubicin, acid and hypoxia/reoxygenation (H/R) conditions, and exosomes were successfully identified by tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…It has been corroborated that circ_0061395 silencing can trigger cell cycle arrest and apoptosis, and suppress the proliferation of HCC in vitro, as well as inhibit tumor growth (56). Similarly, miR-4454 inhibitor-mediated exosomes can substantially exacerbate cycle arrest, apoptosis and the formation of reactive oxygen species in HCC (95). Of note, the progression of HCC is a result of the accumulation of several time-intersecting steps, including invasion, migration, angiogenesis, immune escape and metastasis, and sEV cargos may also function via several mechanisms.…”
Section: Roles Of Sevs In Hcc Tumor Formation and Progressionmentioning
confidence: 88%
See 1 more Smart Citation
“…It has been corroborated that circ_0061395 silencing can trigger cell cycle arrest and apoptosis, and suppress the proliferation of HCC in vitro, as well as inhibit tumor growth (56). Similarly, miR-4454 inhibitor-mediated exosomes can substantially exacerbate cycle arrest, apoptosis and the formation of reactive oxygen species in HCC (95). Of note, the progression of HCC is a result of the accumulation of several time-intersecting steps, including invasion, migration, angiogenesis, immune escape and metastasis, and sEV cargos may also function via several mechanisms.…”
Section: Roles Of Sevs In Hcc Tumor Formation and Progressionmentioning
confidence: 88%
“…The development of HCC can be partly attributed to the rapid proliferation and uncontrolled expansion of tumor cells, which also accounts for tumor progression and resistance to therapy. sEVs mediate tumor growth and expansion by affecting the cell cycle, proliferation rate and apoptosis of HCC cells (93)(94)(95). Cao et al (71) suggested that exosomal miR-21 can influence HCC by altering the expression of the tumor suppressor genes, PTEN and PTEN pseudogene 1.…”
Section: Roles Of Sevs In Hcc Tumor Formation and Progressionmentioning
confidence: 99%
“…miRNA-4301 and miRNA-5100 have been observed to regulate proliferation and apoptosis in lung and breast cancer cells [ 64 , 65 , 66 , 67 ], but according to our assessment there are no reports on their implication in hepatic diseases. For miRNA-4454 , it was reported that upregulation positively enhances hepatic carcinoma progression [ 68 ], miR-223 is a common regulator in various liver diseases [ 69 ], and miRNA-3663-3p was shown to be downregulated in hepatocellular carcinoma cells, thus positively regulating cell proliferation of cancer cells [ 70 ]. The involvement of these three miRNAs in liver diseases might pose an interface between their PA-induced upregulation and possible carcinogenic properties that have been described for PAs [ 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…found that the expression of miR-4800-3p was different in colon-adenoma- and colon-cancer-related diseases, which may be used as a non-invasive screening biomarker of colon cancer ( 20 ). In addition, the miR-4800-3p is reported to be highly expressed in HCC tissues and upregulated in exosomes derived from HepG2 cells after treatment with TGF-β ( 21 23 ). However, the influences of miR-4800-3p on the progression of HCC are still unclear.…”
Section: Introductionmentioning
confidence: 99%